Performance and Energy Consumption Evaluation of Embedded Applications: A Method Based on Platform's Behavioral Model - Nogueira, Bruno Costa e Silva; Maciel, Paulo Romero Martins; Tavares, Eduardo Antonio Guimaraes; Carneiro, Ermeson; Callou, Gustavo; Lima, Ricardo Massa Oliveira; Ferraz, Rodolfo; Montenegro, Bruno (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
This paper presents a performance and energy consumption modeling technique for embedded systems. The proposed method adopts a formal model based on Coloured Petri Nets for modeling the functional behavior of processors and memory architectures at a high-level of abstraction. The applicability of the proposed method is illustrated by evaluating a set of applications and a general-purpose microcontroller. Experimental results demonstrate an average accuracy of 96% in comparison with the respective measures acquired from the real hardware platform. Moreover, the high-level behavioral representation of platforms allows the rapid analysis of performance and energy consumption of complex systems.